Parasitoid releases to manage Queensland fruit fly, Bactrocera tryoni, in southeastern Australia - Lucy K. R. McLay; Joanne C. Dawson; J. Paul Cunningham (BioControl, 2026)
Queensland fruit fly, Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), is Australia’s most economically important horticultural pest. Its range has expanded from its ancestral habitat in rainforests of northeastern Australia into southeastern Australia, and commercial crops. Biocontrol using parasitoid wasps has considerable potential in assisting the area-wide management of B. tryoni in southeastern Australia where they are largely absent. We mass-reared and released two species of parasitoid wasp, Fopius arisanus (Sonan) (Hymenoptera: Braconidae) and Diachasmimorpha kraussii (Fullaway) (Hymenoptera: Braconidae), at six locations in southeastern Australia where they were previously absent. Parasitoid persistence and establishment were monitored over three growing seasons through field collection of B. tryoni infested fruit. Both species parasitised B. tryoni in the field and persisted at the release sites within season. Parasitism rates were up to 63% for D. kraussii and 38% for F. arisanus . D. kraussii were recovered at two of four monitored sites a year after the last releases, indicating the potential of this species to establish in southeastern Australia. In a second study we performed choice and no-choice laboratory experiments to determine if either parasitoid species could target and parasitise the tephritid, Urophora stylata (F.) (Diptera: Tephritidae), which is an established classical biocontrol agent for weed thistles. We found no evidence that either parasitoid can parasitise U. stylata . Our studies indicate that F. arisanus and D. kraussii have potential as biocontrol agents as part of integrated pest management and area-wide management for B. tryoni in southern Australia, with D. kraussii as the more promising candidate.